1987
DOI: 10.1007/bf01020156
|View full text |Cite
|
Sign up to set email alerts
|

Inducible versus constitutive PI 227687 soybean resistance to mexican bean beetle,Epilachna varivestis

Abstract: Contrary to constitutive resistance, inducible resistance to Mexican bean beetle (MBB) (Epilachna varivestis) herbivory in PI 227687 soybean leaves was positively correlated with total phenolic content and temporally unique, increasedL-phenylalanine ammonia-lyase (PAL) andL-tyrosine ammonia-lyase (TAL) activities. Initial expression of the induced resistance was localized at or near the site of herbivory. Systemic parameters of the induced resistance also were observed. Inducible MBB resistance in PI 227687 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Many studies have documented changes in plants induced by herbivore feeding or arti®cial damage over some period of time (e.g., Baldwin 1988;Croxford et al 1989;Baldwin et al 1994;McCloud et al 1995), and the existing data generally support the model of the timing of induced resistance described above. However, most studies have looked at induced resistance over short periods of time, and many have not followed their systems through the full decay of induced responses (e.g., Edwards et al 1985;Chiang et al 1987;Olson and Roseland 1991;Stout et al 1996). It is therefore not yet clear that we have a complete picture of the time course of induced resistance.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies have documented changes in plants induced by herbivore feeding or arti®cial damage over some period of time (e.g., Baldwin 1988;Croxford et al 1989;Baldwin et al 1994;McCloud et al 1995), and the existing data generally support the model of the timing of induced resistance described above. However, most studies have looked at induced resistance over short periods of time, and many have not followed their systems through the full decay of induced responses (e.g., Edwards et al 1985;Chiang et al 1987;Olson and Roseland 1991;Stout et al 1996). It is therefore not yet clear that we have a complete picture of the time course of induced resistance.…”
Section: Introductionmentioning
confidence: 96%
“…Alterable (inducible) resistance in plants to herbivory and other environmental stresses is well documented (Kogan & Paxton, 1983;Chiang et al, 1987;Heinrichs, 1988); however, more emphasis should be placed on the fact that a plant's response to such environmental stimuli may range from maximized resistance to maximized susceptibility (Neupane & Norris, 1990;Haanstad & Norris, 1991). Specific responses are influenced especially by the plant species and cultivar, the overall plant physiological status, the specific involved leaf or other plant organ, the dosage of the elicitor, the method of elicitor application and the time interval since exposure (treatment) (Neupane & Norris, 1990;Haanstad & Norris, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…SBL is a general plant feeder and its host range includes members of 28 plant families (Herzog, 1980). The role of induced factors in the resistance of soybean to herbivores is only beginning to be unravelled, but recent studies have shown that soybean resistance to the MBB increases in response to extrinsic stress factors, including UV radiation (Hart et al, 1983), mechanical injury and fungal cell wall suspension (Lin & Kogan, unpublished), and insect herbivory (Chiang et al, 1987;Lin & Kogan, unpublished). Growth rates of SBL larvae decreased when larvae were reared on soybean leaves from plants that had been mechanically injured (Reynolds & Smith, 1985).…”
Section: Introductionmentioning
confidence: 99%